The Vie de Saint Alexis in the Twelfth and Thirteenth Centuries : An Edition and Commentary - Elliott, Alison Goddard (Book collections on Project MUSE., 1983)
The first work of genuine literary merit in Old French is theVie de saint Alexis, and later reworkings of it attest to its popularity. This volume offers two editions: a twelfth-century edition that was published inaccurately by Gaston Paris, and a thirteenth-century version that has not been published. These two revisions tell us a great deal about changing tastes and interests in the Middle Ages, and their implications exceed that of the fate of a particular work.